Warfare on the Mediterranean in the age of sail a history, 1571-1866 - Blackmore, David S. T. (McFarland & Co., 2011)
"Between the last battle fought entirely under oars in 1571 and the first fought entirely under steam in 1866, naval warfare in the Middle Seas and adjacent Atlantic waters was dominated by the sailing warship. This exploration of that period in military history begins with an overview of the galley warfare and a discussion of the technological developments"--Provided by publisher.